The attitudinal and demographic factors as determinant of performance appraisal / Sarminah Samad - Samad, Sarminah (Universiti Teknologi MARA Cawangan Pahang, 2007)
This paper presents the findings of a study, which investigated how perception of attitudinal and demographic factors played a significant role on employees’ performance appraisal. A total of 584 managerial level of employees in Telekom Malaysia (TM) were selected as a sample based on the stratified random sampling. The study used self-administered questionnaire as the research instrument. The data obtained were analyzed using descriptive and inferential statistics. The results hypothesized that both attitudinal and demographic factors perceptions are positively related to performance appraisal. The study revealed that attitudinal and demographic factors made significant contribution to employees’ performance appraisal. Among all the factors, job satisfaction facet of salary appeared to be the most significant determinant of employee’s performance appraisal. Based on the implication of the research findings, several suggestions were put forward.